Answer:
B
Step-by-step explanation:
Not all of the pairs represent the same ratio
Answer:
describe the relationship between what
Step-by-step explanation:
31 degrees, 31 degrees, 118 degrees
Step-by-step explanation:
Step 1 :
Let x be the measure of 2 angles of the given isosceles triangle with same measure
Let y be the measure of 3rd angle
So we have x + x + y = 180
Step 2 :
Given that the measure of 3rd angle of triangle is 25° more than three times the measure of either of the other two angles
So we have , y = 3 x + 25
Step 3:
Substituting for y in the first equation we have,
x + x + 3 x + 25 = 180
=> 5 x + 25 = 180
=> 5 x = 180-25 = 155
=> x = 155/5 = 31
Hence the 2 angles of the triangle are 31 degrees.
Step 4:
we have y = 3 x + 25
=> y = 3 * 31 + 25 = 118
Hence the 3rd angle of given triangle is 118 degrees
Following expressions will have negative product
![(\frac{1}{2})(-\frac{1}{2})\ and\ (-\frac{1}{2})(\frac{1}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B2%7D%29%28-%5Cfrac%7B1%7D%7B2%7D%29%5C%20and%5C%20%28-%5Cfrac%7B1%7D%7B2%7D%29%28%5Cfrac%7B1%7D%7B2%7D%29)
Following expressions will have positive product
![(-\frac{1}{2})(-\frac{1}{2})\ and\ (\frac{1}{2})(\frac{1}{2})](https://tex.z-dn.net/?f=%28-%5Cfrac%7B1%7D%7B2%7D%29%28-%5Cfrac%7B1%7D%7B2%7D%29%5C%20and%5C%20%28%5Cfrac%7B1%7D%7B2%7D%29%28%5Cfrac%7B1%7D%7B2%7D%29)
Further explanation:
We will see at each expression one by one
First expression is:
![(-\frac{1}{2})(\frac{1}{2})](https://tex.z-dn.net/?f=%28-%5Cfrac%7B1%7D%7B2%7D%29%28%5Cfrac%7B1%7D%7B2%7D%29)
In the given expression one term is positive and one term is negative. The product of negative and positive terms is negative.
Second Expression is:
![(-\frac{1}{2})(-\frac{1}{2})](https://tex.z-dn.net/?f=%28-%5Cfrac%7B1%7D%7B2%7D%29%28-%5Cfrac%7B1%7D%7B2%7D%29)
Both terms are negative and the product of two negative terms is positive.
Third Expression is:
![(\frac{1}{2})(-\frac{1}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B2%7D%29%28-%5Cfrac%7B1%7D%7B2%7D%29)
The expression has one positive and one negative term so the product will be negative
Fourth Expression is:
![(\frac{1}{2})(\frac{1}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B2%7D%29%28%5Cfrac%7B1%7D%7B2%7D%29)
Both terms are positive so the product will also be positive
Keywords: Product, Expressions
Learn more about expressions at:
#LearnwithBrainly